Respuesta :

(A) Product of [tex]-2x^{3}+x-5[/tex] and [tex]x^{3}-3x-4[/tex] is:

[tex](-2x^{3}+x-5)(x^{3}-3x-4)[/tex]

[tex]=-2x^{3}(x^{3}-3x-4)+x(x^{3}-3x-4)-5(x^{3}-3x-4)[/tex]

[tex]=(-2x^{3})(x^{3})+(-2x^{3})(-3x)+(-2x^{3})(-4)+x(x^{3})+(x)(-3x)+(x)(-4)+(-5)(x^{3})+(-5)(-3x)+(-5)(-4)[/tex]

[tex]=-2x^{6}+6x^{4}+8x^{3}+x^{4}-3x^{2}-4x-5x^{3}+15x+20[/tex]

[tex]=-2x^{6}+6x^{4}+x^{4}+ 8x^{3}-5x^{3}-3x^{2}-4x+15x+20[/tex]

[tex]=-2x^{6}+7x^{4}+3x^{3}-3x^{2}+11x+20[/tex]

(B) Yes.

Product of [tex]-2x^{3}+x-5[/tex] and [tex]x^{3}-3x-4[/tex] = Product of [tex]x^{3}-3x-4[/tex] and [tex]-2x^{3}+x-5[/tex] because multiplication is commutative.

Commutative Property of multiplication says that a.b = b.a.

Thus, multiplication is same irrespective of the order of two numbers.



ACCESS MORE